Reduced plasma ascorbic acid levels in recipients of myeloablative conditioning and hematopoietic cell transplantation. (1st August 2019) - Rasheed, Mahmood; Simmons, Gary; Fisher, Bernard; Leslie, Kevin; Reed, Jason; Roberts, Catherine; Natarajan, Ramesh; Fowler, Alpha; Toor, Amir
Abstract: Hematopoietic cell transplantation (HCT) conditioned using myeloablative conditioning (MAC) is complicated by end organ injury due to endothelial dysfunction and graft versus host disease. Mucositis and oxidant injury results in micronutrient deficiency. Ascorbic acid (AA) levels were measured in 15 patients undergoing HCT conditioned with MAC (11 allogeneic and four autologous HCT). Ascorbate levels declined postconditioning to 27.3 μMol/L (±14.1) by day 0 ( P = .03 compared with pretransplant baseline), reaching a nadir level of 21.5 (±13.8) on day 14 ( P = .003) post‐transplant. Patients undergoing allogeneic HCT continued to have low AA levels to day 60 post‐transplant. The role of AA in maintaining endothelial function and hematopoietic as well as T‐cell recovery is provided, developing the rationale for repletion of vitamin C following HCT.